Analisa prevalensi dan derajat infeksi parasit pada ikan Jelawat (Leptobarbus hoevenii ) di Kecamatan Seruyan Hilir, Kalimantan Tengah - Sri Herlina (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
This study aims to identify the types of parasites, the part of the body that was attacked, the prevalence and degree of ectoparasitic infections in Hoven’s carp (Leptobarbus hoevenii). Sampling was conducted in two Villages in Seruyan Hilir District with a sample size of 30 fish. The rate of transmission of ectoprasite is calculated using the prevalence and degree of infection of the ectoparasite attack. Descriptive analysis is used to describe the level of ectopracite attack on Hoven’s carp. The results showed that the types of ectoparasites that were found were 3 types that infect on Hoven’s carp. Namely Dactylogyrus sp (Plathyhelminthes), Trichodina sp, and Ichtyophtirius multifiliis (Cilliphora). The value of the prevalence and degree of ectoparasitic infection that infects on Hoven’s carp ranges from 16.6 to 75% and 1.4-2.5 individuals /fish. Keywords : Hoven’s carp (Leptobarbus hoevenii), ectoparasite, prevalence, infection